Influence of spray and combustion processes on piston temperatures and engine heat transfer in a high-output diesel engine. (May 2023) - Tess, Michael J; Korivi, Vamshi; Gingrich, Eric; Schihl, Peter
Simultaneous measurements of global engine heat transfer and subsurface piston temperatures were utilized to evaluate the potential of an extended duration combustion event to minimize heat rejection in a diesel engine. The combustion duration was parametrically varied by changing the injector orifice diameter (0.167, 0.196, and 0.230 mm) and fuel injection pressure (110–200 MPa) while exploring three high-output operating conditions. This investigation was limited to a single-pulse injection strategy while holding engine load constant to represent operating points at rated power and peak torque. For a constant combustion phasing, the results suggest the duration of the spray and combustion processes did not greatly influence gross indicated thermal efficiency (ITEg) or global heat transfer from the engine, except for extremely long combustion durations of approximately 50 crank-angle degrees or longer. At the longest combustion durations, there was a negative impact on ITEg and global heat transfer. Analysis of the steady-state piston temperature measurements at constant CA50 revealed two interesting, and opposite, trends: as the combustion duration was increased through a smaller orifice diameter injector, the piston temperatures increased by up to 60°C locally on the bowl rim; in contrast, as the combustion duration was increased through lower injection pressures, the piston temperatures decreased by up to 80°C locally on the bowl rim. CFD simulations coupled with a conjugate heat transfer model of the piston predicted the piston heat flux at the highest load operating condition. The CFD results qualitatively agreed with the piston temperature measurements in supporting the conclusion that orifice diameter had a stronger effect on piston heat flux than injection pressure. Overall, this research provides directional trends to engine designers and calibrators for optimizing the injection parameters for decreased engine heat transfer and managing piston temperatures.